Efek Pemberian Massage Effleurage Mampu Meningkatkan Produksi Air Susu Ibu pada Ibu Nifas - Margareta Rinjani; Magdalena Tri Putri Apriyani (Jurnal Kesehatan Metro Sai Wawai, 2021)
Background: The problem with the target of the exclusive breastfeeding program has not yet reached the global target due to the factor that mothers who give birth think that breastfeeding has not been smooth. The solution can be done with non-pharmacological therapy, oxytocin massage, effleurage massage, by involving and supporting the husband. Purpose: This study was to examine the effect of oxytocin massage through effleurage massage on breast milk production in postpartum mothers. Methods: Quasi experimental with nonequivalent control group as the design of this study. The treatment group was 17 normal postpartum pregnant women and 17 control groups. The treatment group after 6-8 hours postpartum was given effleurage massage on the back using olive oil for 3-5 minutes. Data analysis using Mann-Whitney test. Results: The results showed that there was an effect before and after effleurage massage was carried out in the experimental and control groups, namely (p = 0.002). Conclusion: Non-pharmacological therapy with oxytocin massage through effleurage massage was able to increase the amount of milk production by involving and supporting the husband.Latar belakang: Masalah target program pemberian ASI (Air Susu Ibu) eksklusif masih belum mencapai target global disebabkan oleh faktor ibu bersalin menganggap ASI belum lancar. Solusi dapat dilakukan dengan terapi nonfarmakologi pijat oksitosin massage effleurage dengan melibatkan dan dukungan suami. Tujuan: Studi ini untuk mengkaji pengaruh pijat oksitosin melalui massage effleurage terhadap produksi ASI pada ibu postpartum. Metode: Quasi eksperimental dengan nonequivalent control group sebagai rancangan studi ini. Kelompok perlakuan adalah ibu hamil postpartum normal berjumlah 17 dan kelompok kontrol 17 orang. Kelompok perlakuan setelah postpartum 6-8 jam diberikan massage effleurage di bagian punggung dengan menggunkan minyak zaitun selama 3-5 menit. Analisis data menggunakn Uji Mann-whitney. Hasil: Hasil menunjukkan terdapat pengaruh sebelum dan sesudah dilakukan massage effleurage pada kelompok eksperimen dan kontrol yaitu (p=0,002). Simpulan: Terapi nonfarmakologi dengan pijat oksitosin melalui massage effleurage mampu meningkatkan jumlah produksi ASI dengan melibatkan dan dukungan suami.   w:LsdException L